Peningkatan Mutu Produksi Tanaman Siong Di Kecamatan Basse Sangtempe Utara - Busra Bumbungan; Masluki Masluki; Mutmainnah Mutmainnah (Journal of Innovation and Applied Technology, 2018)
Siong is one of the economical valuable crops that grown in North Basse Sangtempe, Luwu. This plant grows wildly around the society. However, many farmers do not understand the economic potential of this plant due to low knowledge of farmer on proper cultivation techniques and post harvest handling of siong plant. The products produced of siong plant are black cincau and the siong tea that will be focus of ibm activities program that conducted in the village of Bonglo and Tede. The IbM activities conducted through the input of cultivation technology and post harvest, can improve the quality of siong plant production and certainly increase the farmers income. In addition, this knowledge can be transferred to other farmers so it can help them in developing siong plants into plants that can be cultivated intensively in North Basse Sangtempe not only in the village of Bonglo and Tede. The team provides solutions that implemented in the IbM program including: knowledge on how to seed, how to plant until how to harvest and post harvest of siong plant. High fiber content of siong plant provides a lot of benefits for the health of body adequate intake for dietary fiber to mantain health.